Extracellular synthesis of nanoselenium from fresh water bacteria Bacillus sp., and its validation of antibacterial and cytotoxic potential. (August 2020) - Bharathi, S.; Kumaran, S.; Suresh, G.; Ramesh, M.; Thangamani, V.; Pugazhvendan, S.R.; Sathiyamurthy, K.
Abstract: In this present study, selenium reducing bacteria were isolated from fresh water pond. The cell free supernatant from B2 strain was found to effectively reduce sodium selenite and was identified as Bacillus sp. based on 16S r RNA sequencing. The selenium nanoparticles (Se NPs) synthesised using Bacillus sp. B2 were characterised by UV- spec, XRD, FTIR, FESEM and EDX. The selenium nanoparticles exhibited maximum peak at 280 nm in UV spectrophotometric analysis due to the surface plasmon resonance. FTIR analysis of cell free supernatant from Bacillus sp. B2 and synthesised selenium nanoparticles reveals that the proteins were mainly responsible for the reduction and stabilisation of Se nanoparticles. The XRD pattern shows the synthesised Se NPs were crystalline in nature with the average size of 33.2 nm. The SEM analysis reveals the Se NPs are spherical in shape with the size range of 20-50 nm and EDX pattern shows selenium exist as major element. The antibacterial activity of the Se NPs shows activity against all the tested bacteria. The lowest MIC and MBC of Se NPs was 8 μg/200 μL against Pseudomonas aeruginosa (NCIM 5031) . The cytotoxicity of SeNPs against Human non-small lung cancer cell line A549 was tested by MTT assay that showed IC50 value of 3 μg/mL. The ET/AO staining of the Se NPs treated cells further revealed the result. Based on this we conclude that fresh water bacteria Bacillus sp. B2 can be used for selenium nanoparticles synthesis which is an ecofriendly and easy process for biomedical applications. Highlights: A rapid protocol for synthesis of Se NPs using fresh water bacteria Bacillus sp. B2 was developed. The synthesised Se NPs showed antibacterial activity against both gram positive and gram negative bacteria. The cytotoxicity of Se NPs against A549 cell line was assessed by MTT assay that showed IC50 value of 3µg/ml. Hence the Se NPs from Bacillus sp. B2 with therapeutic potentials and can be effectively used in the biomedical research.